The Influence of Return on Assets (ROA) and Return on Equity (ROE) on Stock Prices of Transportation and Logistics Companies Listed on the Indonesia Stock Exchange - Septriawan, Muhammad Reza; Rozi, Fachrul; Syaharman, Syaharman (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
This study investigates the influence of Return on Assets (ROA) and Return on Equity (ROE) on stock prices of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. A quantitative research method was employed using secondary data derived from audited financial statements. Eight companies were selected using purposive sampling, and data analysis was conducted through multiple linear regression with SPSS 25. The findings indicate that ROA has a significant negative effect on stock prices, while ROE has no significant impact. However, both variables jointly influence stock prices significantly, with an adjusted R² of 0.820, suggesting that 82% of stock price variation can be explained by ROA and ROE. The results highlight the need for investors to consider sector-specific dynamics and for companies to align financial performance with market expectations. This study contributes to the financial literature by providing insights into the stock valuation process in asset-intensive industries and offers practical recommendations for investors, managers, and regulators.